Faktor-Faktor yang Mempengaruhi Keputusan Wanita Dewasa Dini untuk Tetap Berpacaran dengan Kekerasan: Tinjauan Pustaka - Shavira Vandya Maharani; Tience Debora Valentina (Universitas Kristen Maranatha, 2023)
Abusive Dating Relationship is a type of violence that ranks first among types of violence in the personal realm. But even though the victim has experienced violence and even had many things shackled from their life, victims tends to still accept and give a chance back to the partner who committed the violent act by taking a lot of consideration in deciding to leave the Abusive Dating Relationships that influenced by many factors. This literature review aims to find out what factors can influence or contribute to a woman's decision-making process to stay in an Abusive Dating Relationship. Results shows there are factors that influence adult women's decision to stay in an Abusive Dating Relationship are commitment to the relationship, social support, learned helplessness, perceptions and expectations, history of abuse and childhood trauma, social systems and beliefs, dependence on partners, social demands, positive reinforcement, and investment and satisfaction in relationships.